Cellular and organisational team formations for effective Lean transformations. Issue 1 (1st January 2018) - De Vries, Herbert; Van der Poll, H. M.
ABSTRACT: Teamwork is considered essential for effective Lean organisations. However, how and why are teams formed during a successful Lean transformation relative to changes in organisational structure? Constructs for variables and factors that influence formation of teams, during and after Lean transformation maturity, were identified. The research employed a purposively sampled case study with three questionnaires, focus groups, interviews and multiple linear regression. Self-directed teams become flow-line or cellular-work teams, supported by dedicated cross-functional teams led by first line managers who run manufacturing cells as small business units. Participation of cellular team members leads to ongoing commitment and continuous improvement within the team leading to restructuring of organisations for effective flow and pull. Cross-functional team activity and self-directed team activities are vital components for successful Lean transformations. Constructive, humble, and common-sense leadership is required for team formations. Future research could investigate literacy coupled with Lean transformations for South African organisations. Abbreviations: TPS: Toyota production system; JSE: Johannesburg stock exchange; SMED: single minute exchange of die; TW: Teamwork; PARTINV: Participation and Involvement; CELFM: Cellular Format – self-directed team activity; LHINT: Level of Horizontal Integration – cross-functional team activity; LOCDM: Locus of Decision-Making – by organisational level; TAG: Taguchi; CTR: Cycle Time Reduction; 5S: Five-S; TPM: Total Productive Maintenance; KAN: Kanban pull; VIS: Visibility; KAIZ: Kaizen; HOSHK: Hoshin Kanri; 7W: Seven wastes; PROB: Problem solving; STAND: Standard work; SPF: One Piece Flow; CM: Cellular Manufacturing; HEIJ: Heijunka; DISTVAL: Value per customer; VSM: Value Stream Mapping; POKJID: Mistake proofing; SMED: One digit exchange of die; POLDEP: Policy Deployment